Health Literacy, Label Comprehension, and Consumer Perceptions of Quasi-Drug Information Among Korean Adults: A Cross-Sectional Study - Ko Y; Kim HJ; Lee SM (Risk Management and Healthcare Policy)
Youngill Ko,1,2,* Heui Jae Kim,3,* Seung-Mi Lee1 1College of Pharmacy, Daegu Catholic University, Gyeongsan, Republic of Korea; 2The Gyeongbuk Pharmaceutical Association, Gumi, Republic of Korea; 3Pharmacy Department, Daehang Hospital, Seoul, Republic of Korea*These authors contributed equally to this workCorrespondence: Seung-Mi Lee, College of Pharmacy, Daegu Catholic University, 13-13 hayang-ro, Hayang-eup, Gyeongsan, 38430, Republic of Korea, Email seungmi2011@gmail.comPurpose: Health literacy (HL) is crucial in understanding labels of healthcare products. This study aimed to evaluate HL and its impact on comprehending quasi-drug labels, assess consumer perceptions of key label elements and their perceived importance, and provide actionable recommendations for improving label design and health communication.Methods: An online cross-sectional survey of 500 Korean adults (aged 20– 69) was conducted in September 2023 using proportionate stratified sampling based on the 2020 Korean Census. HL was assessed using the Korean Rapid Estimate of Adult Literacy in Medicine (REALM-K). The survey included demographic data, quasi-drug usage patterns, comprehension of 63 quasi-drug terms, and perceptions of label elements. A 5-point Likert scale was used to assess the importance, agreement, and need for improvement of label elements, and statistical analyses included descriptive statistics, chi-square tests, t-tests, Pearson correlation, and logistic regression.Results: Most participants had inadequate HL (68.4%). Adequate HL is strongly associated with higher comprehension of quasi-drug terms (r = 0.783, p < 0.001). Older age (60– 69 years, AOR = 5.97, 95% CI: 1.74– 20.48) and adequate HL (AOR = 28.54, 95% CI: 9.68– 84.15) positively influenced comprehension. Participants with adequate HL rated the importance of label elements, such as “ingredient name” (mean = 4.02, SD = 0.79, p = 0.015) and “contraindications” (mean = 4.68, SD = 0.57, p < 0.001), higher than those with inadequate HL.Conclusion: Significant disparities exist in the comprehension and perceived importance of quasi-drug label elements based on HL levels among Korean adults. Findings emphasize the need for targeted strategies, such as using simplified language and visual aids, to enhance label comprehension. These interventions could improve public health outcomes by increasing understanding of quasi-drug information across diverse HL levels. Future research should focus on developing and testing these targeted interventions to bridge the identified comprehension gap.Keywords: health literacy, quasi-drugs, label comprehension, communication, Korean adults